Tem Gene Detection as ESBL Marker in Clinical Isolates Klebsiella pneumoniae : A Case Study - Arafah Nurfadillah; Wahdaniar; Miladiarsi; Ade Irma; Tenri Ayu Adri (Journal of Health Sciences and Medical Development, 2022)
Klebsiella pneumoniae is one of the most common ESBL-producing microorganisms. The research aims to detect the Tem gene in clinical isolates of K. pneumonaie from the Laboratory of clinical pathology of Wahidin Sudirohusodo General Hospital. Methods: This research is a descriptive cross-sectional design. Fifty samples of K. pneumonieae were obtained from the Laboratory of clinical pathology from March to May 2018. Tem gene was detected using primary Tem 164.SE and Tem 165.AS (445 bp) of Polymerase Chain Reaction (PCR). The research results indicate that 48 isolates are positive, containing the Tem gene with the highest number found in the sputum specimen. Genotype detection of bacteria-producing ESBL is essential so that antibiotic therapy given to the patients is more effective and efficient.